CONVERSATIONAL IMPLICATURE IN THE GREEN BOOK MOVIE - Hidayati, Fitrah; Mahmud, Murni (Faculty of Languages and Literature, Universitas Negeri Makassar, 2022)
This study was aimed at accomplishing two objectives: (1) to identify the types of conversational implicature found in the Green Book movie and (2) to discover the functions of each conversational implicature found in the main characters' dialogue in the Green Book movie. The data in this study were taken from dialogue of the main characters in the Green Book movie 2018. The researchers used a qualitative method to analyze the data and to find out the types of conversational implicature. The researchers used conversational implicature theory by Paul Grice, and used the theory of Roman Jacobson to find out the function of implicature. The result of this study indicates the process of identifying conversational implicature, the type of implicature, and the function. The types of implicature that occur are generalized and particularized. There are 19 cases identifying conversational implicature: 12 data identifying generalized conversational implicature, and 7 data identifying particularized conversational implicature. Implicatures in this movie have four types of language function named metalinguistic, conative, emotive, and referential. First, the kind of conversational implicature commonly occurs in the Green Book movie is Generalized Conversational Implicature because it is used in daily conversation so the listeners do not need specific knowledge to interpret the meaning. And then, there are two kinds of language function that are dominant found in this study, which are the conative and the referential. It showed the implicature that implied by the main character in the movie are concerned with (1) influencing the behavior of the addressee or convey the speaker’s commands, (2) providing the actual information based on the situation in the movie.